Juridical Analysis of The Authority of The Civil Services Police Unit In Enforcement of The Minister of Home Affairs Regulation No. 26 of 2005 (Study of Simalungun Regency Eassay) - Delfin Mikhael Meliala (Journal of Law Science, 2020)
Policeman Guardian Territory Of Jurisdiction that is sets of Equipment Administration Territory in Keep and Execute Calm and Orderliness the public with cause Arrange Territory and Arrange Head Territory. So Squad Policeman Guardian Territory Of Jurisdiction that is sets of Administration in area Arrange Territory, orderlinnes the public, and Calm Society. Squad Policeman Guardian Territory Of Jurisdiction in lead by someone head squad and be in under and be responsible see Head Territory. In order that implementation of the duty Squad Policeman Guardian Territory Of Jurisdiction can power use and result use in best, need to be compass Operational as Procedure Permanent For Squad Policeman Guardian Territory Of Jurisdiction in bring about duty.Be then are become problems in research this form how duty stake and function Squad Policeman Guardian Territory Of Jurisdiction, how Squad Policeman Guardian Territory Of Jurisdiction upgrade professionalism, how compass Procedures Permanent Operational Squad Policeman Guardian Territory Of Jurisdiction. There is even principle research are in take deep research in wear encode for processing primary that is with make interview at side Squad Policeman Guardian Territory Of Jurisdiction of equipment Residence Simalungun with in add by literature with be related to by title and problem. At finish creation this in come together a certain conclusion are form distribution from answer problem are in take away according to brief and in give as well little suggestion at side are related to use go forward with input at rubber side for can in purpose carefully.